Re-Audit of the Physical Health Monitoring of Patients Receiving Antipsychotic Treatment in Ty Llywelyn Medium Secure Unit - Justina Akinlua (BJPsych Open)
Aims: The aim of conducting this audit is to know whether the physical health monitoring of our clients are done appropriately in accordance with the BCUHB guidelines for physical health monitoring for adults prescribed antipsychotic therapy and also to reduce the risk of adverse side effects of antipsychotics on the physical health of our patients.